Association of soy intake and cooking methods with colorectal polyp and adenoma prevalence: findings from the extended Lanxi pre-colorectal cancer cohort (LP3C) - Zheng, Weifang; Lin, Xunan; Zhu, Meng; Ye, Hao; Hu, Xiaodong; Liu, Xiaohui; Hu, Lixiang; Zheng, Youyou; Hu, Peiling; Zhuang, Pan; Jiao, Jingjing; Zhang, Yu (Frontiers in Nutrition, 2024)
Background: Limited research has explored the association between dietary soy products and colorectal polyps and adenomas, with insufficient attention given to cooking methods and subtypes of polyps. This study aimed to comprehensively assess the relationship between soy intake, its cooking methods, and the risk of colorectal polyps and adenomas within a high-incidence population of colorectal cancer (CRC) in China. Methods: Data were derived from 14,903 participants aged 40-80 years, enrolled in the extended Lanxi Pre-colorectal Cancer Cohort (LP3C) between March 2018 and December 2022. This cross-sectional study is based on the participants' baseline information. Long-term dietary information was collected through a validated food frequency questionnaire (FFQ), and colorectal polyps and adenomas were identified through electronic colonoscopy. Employing multivariate logistic regression, results were expressed as odds ratios (ORs) with their corresponding 95% confidence intervals (95% CIs). Results: 4,942 cases of colorectal polyps and 2,678 cases of adenomas were ascertained. A significant positive association was found between total soy intake and the occurrence of polyps/adenomas. Considering cooking methods, a notable increase in polyp risk was associated with the consumption of fried soys while no association was detected for boiled or marinated soys. Furthermore, total soy intake demonstrated associations with large and multiple polyps, polyps Yamade-typed less than II, and polyps across all anatomical subsites. Conclusion: Within the high-risk CRC population in China, increased soy product intake was linked to a higher risk of polyps, primarily attributed to the consumption of fried soys. This suggests that modifying cooking methods to avoid fried soys may serve as a preventive strategy for colorectal polyps.